Criminal Sanctions for Perpetrators of Defamation: An Islamic Criminal Law Perspective - Azhari, Ninti; Ramadani, Ramadani (Al-Adalah: Jurnal Hukum dan Politik Islam, 2025)
This study explores criminal sanctions for defamation offenders from the Islamic criminal law perspective, focusing on applying maqÄá¹£id al-sharÄ«â€˜ah as a normative foundation. The objective is to compare the restorative justice-oriented approach of Islamic criminal law with Indonesia's positive law, particularly the Electronic Information and Transactions Law (UU ITE), which regulates defamation in the digital era. Using a normative juridical method, the research analyzes primary and secondary legal sources to extract relevant principles. The findings reveal that Islamic criminal law employs ta'zir sanctions, which are flexible and oriented toward restoring social harmony, contrasting with the retributive approach of Indonesia's positive law that often leads to legal uncertainty and risks to freedom of expression. Moreover, Islamic criminal law offers mediation and reconciliation-based solutions to mitigate the social impact of defamation. This study suggests integrating the principles of maqÄá¹£id al-sharÄ«â€˜ah into Indonesia's positive legal framework to create more just and balanced regulations. These findings are relevant for policymakers in addressing legal challenges in the digital era and encourage the development of more inclusive approaches to defamation cases.